2016
DOI: 10.1021/acs.nanolett.6b02418
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Promoting Assembly of Metallic and Nonmetallic Nanoparticles into Interfacial Monolayer Films

Abstract: Two-dimensional metal nanoparticle arrays are normally constructed at liquid-oil interfaces by modifying the surfaces of the constituent nanoparticles so that they self-assemble. Here we present a general and facile new approach for promoting such interfacial assembly without any surface modification. The method use salts that have hydrophobic ions of opposite charge to the nanoparticles, which sit in the oil layer and thus reduce the Coulombic repulsion between the particles in the organic phase, allowing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 32 publications
2
98
0
Order By: Relevance
“…An elegant method of obtaining NP 2D arrays is through spontaneous self‐assembly at liquid–liquid interfaces to form metal liquid‐like films (MeLLFs). These are densely packed monolayers of metal NPs self‐assembled at the interface between two immiscible liquids, which can be obtained simply by shaking a non‐water‐miscible organic solvent with a portion of aqueous metal colloid in the presence of a low concentration of a chemical compound (a “promoter” or “modifier”) which promotes particle adsorption at the interface . These mobile arrays have the same characteristics as the best of the deposited NP films in that they are densely packed, electronically coupled monolayers of particles which can readily be prepared on the cm 2 scale at room temperature in minutes with no specialist equipment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An elegant method of obtaining NP 2D arrays is through spontaneous self‐assembly at liquid–liquid interfaces to form metal liquid‐like films (MeLLFs). These are densely packed monolayers of metal NPs self‐assembled at the interface between two immiscible liquids, which can be obtained simply by shaking a non‐water‐miscible organic solvent with a portion of aqueous metal colloid in the presence of a low concentration of a chemical compound (a “promoter” or “modifier”) which promotes particle adsorption at the interface . These mobile arrays have the same characteristics as the best of the deposited NP films in that they are densely packed, electronically coupled monolayers of particles which can readily be prepared on the cm 2 scale at room temperature in minutes with no specialist equipment.…”
mentioning
confidence: 99%
“…Figure illustrates the fabrication process: Initially a mixture of metal colloid and a polystyrene/dichloromethane (DCM) solution was shaken vigorously in the presence of a promoter in a hydrophobic container to form a lustrous and mobile film of NPs at the liquid–liquid interface (Figure a,b). The promoter, which consists of a hydrophobic cation, stabilizes the negatively charged NPs at the liquid‐liquid interface by providing charge‐screening . A hydrophobic container was used so that the DCM wrapped around the aqueous layer, meaning that the MeLLF partly sat at the top surface of the liquid–liquid interface (Figure c).…”
mentioning
confidence: 99%
“…Comparing the results of both in situ atomic force microscopy and grazing incidence X‐ray small‐angle scattering, it is revealed that the average density of the nanoparticles at the interface varies with the concentration of the surfactant and the interaction between the tip and interface can be studied for the local determination of the acting interfacial interactions. Bell and co‐authors have presented a new approach for promoting 2D interfacial assembly of metal nanoparticles via the utilization of salts that possess oppositely charged hydrophobic ions to that of the nanoparticles residing at the organic layer. As a result, the coulombic repulsion between the particles in the oil phase is reduced that renders the particles to remain in close proximity to the interface.…”
Section: Self‐assembly Of Nanoparticles At Liquid–liquid Interfaces: mentioning
confidence: 99%
“…In situ SERS monitoring of the headspace above the cultures used a SERS substrate composed of a densely‐packed monolayer of dry Ag or Au particles deposited onto a quartz window from a metal‐like liquid film created by assembling the particles at a water/dichloromethane interface . Data on characterisation of the Ag and Au substrates can be found in the Supporting Information (Figure S1).…”
Section: Figurementioning
confidence: 99%